Applying Rituximab During the Conditioning Regimen Prevents Epstein–Barr Virus Infection Following Allogeneic Hematopoietic Stem Cell Transplant in a Children’s Cohort: A Retrospective Case–Control Study - Yongsheng Ruan; Libai Chen; Tingting Luo; Danfeng Xie; Wei Cao; Xuan Liu; Qiujun Liu; Yuhua Xiao; Cuiling Wu; Jianyun Wen; Juan Li; Jiangnan Meng; et al. (Infectious Diseases and Therapy, 2023)
Abstract Introduction Since hematopoietic stem cell transplant (HSCT) is an important therapy for malignant and non-malignant pediatric diseases, improving transplant-related mortality remains a challenge. Currently, rituximab, a monoclonal antibody of anti-CD20, is widely used for several post-HSCT complications. However, few studies have focused on the application of rituximab before HSCT. Methods We conducted a retrospective case–control study from January 2019 to July 2021 to determine this effect in a single center. Forty-eight patients were included in the rituximab group, with a one-to-one ratio matched to the control group. Results Both the occurrence rate and cumulative incidence rate of Epstein–Barr virus (EBV) infection were significantly lower in the rituximab group than in the without-rituximab group (10.4% vs. 33.3%, p = 0.014 and 12.2% vs. 39.3% p = 0.0026, respectively). Furthermore, without the application of rituximab was identified as a risk factor for post-HSCT EBV infection via both univariate [hazard ratio (HR) = 4.17, 95%CI (1.52–11.43), p = 0.005] and multivariate analyses [HR = 4.65, 95%CI (1.66–13.0), p = 0.003]. Although the overall survival (OS) probability of the rituximab group was comparable to the without-rituximab group, a markedly improved OS of the rituximab group was found in the malignant disease subgroup (78.9% vs. 42.1%, p = 0.032). The outcomes of graft-versus-host disease, neutrophil and platelet engraftment, other viral infections, and the reconstitution of lymphocytes showed no significant differences between the two groups. Conclusions The administration of rituximab before HSCT may prevent EBV infection following HSCT.